Sensitivity of Different MRI-Techniques to Assess Gray Matter Atrophy Patterns in Alzheimer’s Disease is Region-Specific - Clerx, L.; Jacobs, H.I.L.; Burgmans, S.; Gronenschild, E.H.B.M.; Uylings, H.B.M.; Echavarri, C.; J. Visser, P.; R.J. Verhey, F.; Aalten, P. (Current Alzheimer Research, 2013)
The present study compares four different structural magnetic resonance imaging techniques used to measure gray matter (GM) atrophy in Alzheimer’s disease (AD): manual and automated volumetry, cortical thickness (CT) and voxel-based morphometry (VBM). These techniques are used interchangeably in AD research and thus far it is unclear which technique is superior in detecting abnormalities early in the disease process. 18 healthy participants without any memory impairment, 18 patients with MCI, and 17 patients with mild AD were included and between-group differences were investigated in AD signature regions (areas in the prefrontal cortex (PFC), medial temporal lobe (MTL) and posterior parietal cortex (PPC)). Both manual volumetric measurements and VBM were able to detect GM atrophy in the early stages (differentiation controls and MCI), mainly in the MTL. In the early phase, automated volumetric measurements showed GM differences in the PPC but not in the MTL. In our sample, CT measurements were not sensitive for group differences in the early stages. PFC regions showed abnormalities in the later stages (controls vs AD) when manual volumetric measurements or VBM are employed. Manual volumetric measurements together with VBM are preferred techniques for assessing GM differences showing abnormalities in most of the investigated regions, with a predominance of the MTL in the early phase. Automated FreeSurfer volumetric measurements show similar performances in the early phase, displaying group differences in the PPC but not in MTL regions. Measurements of CT are less sensitive in the MCI stage and its sensitivity is restricted to the MTL and PPC regions in later stages of the disease (AD).
Keywords: Alzheimer’s disease